Effects of inflammation in dental pulp cell differentiation and reparative response - Lorencetti-Silva, Francine; Sales, Larissa Sthefani; Lamarque, Giuliana de Campos Chaves; Caixeta, Giovana Amorim; Arnez, Maya Fernanda Manfrin; Faccioli, Lúcia Helena; Paula-Silva, Francisco Wanderley Garcia (Frontiers in Dental Medicine, 2022)
The responsiveness of the dentin-pulp complex is possible due to the stimulation of dental pulp cells, which begin to synthesize and secrete dentin matrix. The inflammatory process generated by harmful stimuli should be understood as a natural event of the immune response, resulting in the recruitment of hematopoietic cells, which cross the endothelial barrier and reach the site affected by the injury in order to eliminate the damage and provide an appropriate environment for the restoration of homeostasis. The repair process occurs in the presence of adequate blood supply, absence of infection, and with the participation of pro-inflammatory cytokines, growth factors, extracellular matrix components, and other biologically active molecules. Prostaglandins and leukotrienes are bioactive molecules derived from the oxygenation of arachidonic acid, as a result of a variable range of cellular stimuli. The aim of this review is to describe the process of formation and biomineralization of the dentin-pulp complex and how pro-inflammatory events can modify this response, with emphasis on the lipid mediators prostaglandins and leukotrienes derived from arachidonic acid metabolism.